Implementasi Pengembangan Kurikulum Berkarakter Pesantren (Studi Kasus di MA Mambaul Hikmah Talang Kabupaten Tegal) - Romadlon, Hanif; Mubarok , Taukhid (EDUCATIVA, 2023)
Graduates of formal education, especially those with character, are now starting to fade. Especially in the field of curriculum, it is important for educational institutions to include character values as primary material, given the level of global world needs that require skilled human resources in disciplines that also require character. The implementation of pesantren-based curriculum in schools is an alternative solution for managers of both formal and non-formal institutions for revival in the current era. MA Mambaul Hikmah Talang, Tegal Regency is quite representative in meeting the needs of character education. So it is interesting to be researched about what efforts are made by the management of MA Mambaul Hikmah Talang Kab. Tegal in facing the current educational paradigm, especially developments in the field of curriculum implementation. The primary data source of this research, the author conducted field observations and processed documents at MA Mambaul Hikmah Talang Kab. Tegal. While the secondary data of this research is the main books that are closely related to the issue of curriculum. The data collection techniques used include: library research method, interview method, namely collecting data through interviews with directly related parties, observation method and documentation method. Furthermore, it is hoped that this research can slightly 'fix' the perspective on pesantren which is synonymous with conservative ideology and tends to be considered 'rigid' in the face of educational dynamics. In addition, with its new face and accommodative curriculum, it can be seen what kind of implementation of the pesantren character curriculum is carried out, what programs are realized to support its success and most importantly what progress is achieved by MA Mambaul Hikmah Talang, Tegal Regency. Thus, the implementation of the pesantren character curriculum that has been applied to be the 'mainstay' of the madrasa is really proven to be applied to the wider social environment